Effect of Different Cutting Heights of Mechanically Pruned Grapevines cv. Merlot Over Three Consecutive Seasons - Peppi, M.C.; Kania, E.; Talep, R.; Castro, P.; Reginato, G. (South African Journal of Enology and Viticulture, 2017)
The mechanisation of various vineyard operations reduces production costs and labour requirements, thus allowing for the more efficient management of larger vineyards. However, pruning mechanisation has been associated with yield decline (a decrease in fruit production due to the elongation of the fruiting positions out of the trellis system area), over cropping and unstable yields. Furthermore, manual followup has been a common practice for most vineyards subjected to mechanised pruning. A Merlot vineyard was studied for three consecutive seasons in terms of its vegetative and productive aspects, and hand pruning was compared with mechanised alternating pruning strategies. Bud burst was more successful in hand-pruned vines compared to mechanically pruned vines. However, hand pruning took longer and produced a lower yield compared to mechanical pruning. Traditional high (25 cm above the cordon wire) mechanical pruning showed deteriorating characteristics over time in vegetative and yield parameters. Vines pruned at a lower height (12 cm above the cordon wire) in one of the three seasons maintained high production. Despite higher yields, fruit soluble solids, pH and titratable acidity were not altered. The quantity of second-crop fruit from lateral shoots was small and was very similar among treatments. Mechanical pruning at a lower height in one season in general reduces the annual potential yield, but the average and cumulative effects over the years improve compared to using just traditional high mechanical pruning. These long-term effects make it feasible to fully mechanise vineyard pruning and maintain high yields.